LEARNING TO TOUCH THROUGH PHYSICAL EDUCATION (Fiep Bulletin - online, 2011)
In nature, animals with socialization patterns take time to touch, rub or lick each other; in the human world is also lavishes affection through touch and in the case of traumatic events is common to observe how people instinctively hug or put hand on the shoulder of the sufferer, it can also mention the daily episode of the mother who rubs the child after a fall. These daily acts attributed to contact welfare-inducing properties, as history shows it, contact has been planned a resource used for medicinal purposes in many cultures around the world since ancient times. India, China, Egypt, Australia are some countries that have grown complete systems tactile manipulation or massage. The art of touch is as old as man himself and has evolved from the hands of healers and shamans to physicians and scientists of today who have proven their benefits at both the biological and psychosocial. It should include research on the effect kangaroo (Conde, Diaz and Belize, 2008, among others), describes the benefits experience premature infants reaching contact with the skin of the mother, rather than the incubator. Also research on nerve transmission information specifies for touch with affection (Lamarre 2006). In line similar studies by Field (1999) note that the practice of massage therapy in infants and mothers, has a regulatory role in the amount of free cortisol present the children when they compared in the pre and post the application of this type of intervention. The free cortisol in a chemical agent that induces stress and Professional Regulation is necessary for the psychophysical balance and especially vital for the development of synaptic multiplication in the first years of life. It should be emphasized especially the work of Cesana, Jannot, De Souza and Drigo (2004) entitled "Massage and Physical Education: Curriculum Perspectives" who collect information through questionnaires on the importance and need of massage as a tool for teaching and content of Education Physics. Finally, mention the accusations of Neurosciences and policies of UNESCO International (among others) on the priority of educational environments full of affection, tenderness and love contact the recommendations of the renowned pediatrician Brazelton (1999) undisputed authority on issues of early childhood, who advocates the need for more human contact between family, community and baby. All the above has led the author to consider the tactile stimulation as an appropriate strategy and suitable for pedagogical intervention in early education in the context of the experience of Physical Education. Besides its benefits, tactile stimulation is an interesting option to enrich the methodology of Physical Education led to the early years in Venezuela, even relatively young field compared to the path of other countries on research in the early psychomotor . Thus, based on theoretical approaches and research that support the benefits of tactile stimulation, under the Design of Field Research with a qualitative approach of an Action Research, the author developed a series of activities involving massage, direct and indirect contacts (using objects), and tactile experiences for early childhood education with family involvement, especially in the case of babies in the nursery level. Regarding the latter, we designed a plan of Maternal Education focused on the importance of affection expressed massage as part of the care provided in the Program for Community Simoncito school population. The techniques used were observation and interview. The results at both the Little Simon and Little Simon Community level showed an increased frequency of eye contact, rapport in the mother baby dyad. Easier children from preschool to give references on your body schema. Integration mother-infant and father-infant and staff awareness of the ERC Dona Menca toward the practice of tactile stimulation.A